2009
DOI: 10.1371/journal.pone.0007584
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Sensory Basis of a Food Related Two-State Behavior in C. elegans

Abstract: Most animals display multiple behavioral states and control the time allocation to each of their activity phases depending on their environment. Here we develop a new quantitative method to analyze Caenorhabditis elegans behavioral states. We show that the dwelling and roaming two-state behavior of C. elegans is tightly controlled by the concentration of food in the environment of the animal. Sensory perception through the amphid neurons is necessary to extend roaming phases while internal metabolic perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
268
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(290 citation statements)
references
References 24 publications
19
268
3
Order By: Relevance
“…Previous studies found that locomotor activity is linked to an animal's nutritional state; food-stressed animals seek food and increase exploratory behaviour, whereas food-satiated animals decrease exploratory behaviour 7,20,21 . We found that wild-type L1 larvae moved faster than tmc-1(rg1003) mutants on CeMM plates after 30 min of exposure, whereas on food-deprived NGM plates the locomotion rates for both groups of worms were much higher, but equivalent (Fig.…”
Section: Tmc-1 Functions To Retard Growth On Cemmmentioning
confidence: 99%
“…Previous studies found that locomotor activity is linked to an animal's nutritional state; food-stressed animals seek food and increase exploratory behaviour, whereas food-satiated animals decrease exploratory behaviour 7,20,21 . We found that wild-type L1 larvae moved faster than tmc-1(rg1003) mutants on CeMM plates after 30 min of exposure, whereas on food-deprived NGM plates the locomotion rates for both groups of worms were much higher, but equivalent (Fig.…”
Section: Tmc-1 Functions To Retard Growth On Cemmmentioning
confidence: 99%
“…When malnourished, animals seek out a new food source by actively exploring their environment (roaming), whereas animals that are well fed tend to explore less (dwelling) and when fully sated enter a quiescent or sleep-like state (1-3, 8, 9). Transitions between these behavioral states can be regulated by sensory perception of external stimuli and through gut signals or other internal cues that are generated according to food quality (3,4,6).…”
mentioning
confidence: 99%
“…In invertebrates and vertebrates, appetite, locomotor activity, and sleep rhythms are all driven by nutritional state (1)(2)(3)(4)(5)(6)(7). When malnourished, animals seek out a new food source by actively exploring their environment (roaming), whereas animals that are well fed tend to explore less (dwelling) and when fully sated enter a quiescent or sleep-like state (1-3, 8, 9).…”
mentioning
confidence: 99%
See 2 more Smart Citations